Subcellular metal distributions and metallothionein associations in rough-toothed dolphins (Steno bredanensis) from Southeastern Brazil - Monteiro, Fernanda; Lemos, Leila S.; de Moura, Jailson Fulgêncio; Rocha, Rafael Christian Chávez; Moreira, Isabel; Di Beneditto, Ana Paula; Kehrig, Helena A.; Bordon, Isabella C.A.C. [UNESP]; Siciliano, Salvatore; Saint'Pierre, Tatiana D.; Hauser-Davis, Rachel Ann (Elsevier, 2019)
Metals are subject to internal subcellular compartmentalization, altering their bioavailability. Thus, subcellular metal assessments are crucial in biomonitoring efforts. Metal distribution in three subcellular fractions (insoluble - ISF, thermolabile - TLF and thermostable - TSF) were determined by ICP-MS in Steno bredanensis specimens from Southeastern Brazil. Associations between metals, metallothionein (MT) and reduced glutathione (GSH) were also investigated. Differential metal-detoxification mechanisms were observed. MT detoxification was mostly noted for As, Cd, and Pb, while Cu, Cr, Hg, Ni, Se and Ti displayed lower MT-associations. Fe, Zn and Se, on the other hand, were poorly associated to MT, and mostly present in the ISF, indicating low bioavailability. This is the first report on subcellular Sn and Ti distribution in cetaceans and the first in this species in Brazil. Potential protective roles of essential metals against toxic elements are postulated. This study indicates that important biochemical detoxification information is obtained through subcellular fraction analyses in marine mammals.
Keywords: Bioavailability; Cetaceans; Environmental contamination; Metal detoxification; Metalloproteins; Subcellular fractions